Low levels of strigolactones in roots as a component of the systemic signal of drought stress in tomato. Issue 4 (26th September 2016) - Visentin, Ivan; Vitali, Marco; Ferrero, Manuela; Zhang, Yanxia; Ruyter‐Spira, Carolien; Novák, Ondřej; Strnad, Miroslav; Lovisolo, Claudio; Schubert, Andrea; Cardinale, Francesca
Summary: Strigolactones (SL) contribute to drought acclimatization in shoots, because SL‐depleted plants are hypersensitive to drought due to stomatal hyposensitivity to abscisic acid (ABA). However, under drought, SL biosynthesis is repressed in roots, suggesting organ specificity in their metabolism and role. Because SL can be transported acropetally, such a drop may also affect shoots, as a systemic indication of stress. We investigated this hypothesis by analysing molecularly and physiologically wild‐type (WT) tomato ( Solanum lycopersicum ) scions grafted onto SL‐depleted rootstocks, compared with self‐grafted WT and SL‐depleted genotypes, during a drought time‐course. Shoots receiving few SL from the roots behaved as if under mild stress even if irrigated. Their stomata were hypersensitive to ABA (likely via a localized enhancement of SL synthesis in shoots). Exogenous SL also enhanced stomata sensitivity to ABA. As the partial shift of SL synthesis from roots to shoots mimics what happens under drought, a reduction of root‐produced SL might represent a systemic signal unlinked from shootward ABA translocation, and sufficient to prime the plant for better stress avoidance. Abstract : See also the Commentary on this article by Tardieu, 212: 802–804 .